Therapies for Heart Failure: Clinical Updates and Perspectives - Stela Iurciuc; Dragoș Cozma; Cristina Tudoran (Journal of Clinical Medicine, 2026)
Although signs and symptoms of heart failure (HF) have been described since ancient times, and the term has evolved throughout history, there are still unanswered questions concerning its pathophysiology and best treatment options [...]